Analisis Dan Desain Dinamis Pondasi Dangkal Berdasarkan Data CPT - Putera Agung Maha Agung; Josua Sijabat; Nadia Shofi Khairunnisa (Journal of Applied Civil Engineering and Infrastructure Technology, 2020)
A generator set used at the building has to consider some environmental factors so that it would not affect the building structure system and not cause some noises as long as operation time. In order to avoid these disturbances, all foundation systems are not only analyzed and designed in the static calculation but also they must consider some impact factors due to dynamic loading. This study's purpose is to determine the dimensions of shallow foundation and specifications of rubber as a vibration damper in accordance with applicable regulations. The static calculation analyzes the immediate and consolidation settlements, and bearing capacity that occurred at the soil foundation using the Schmertmann method. The dynamic analysis calculates some magnitudes of frequency and or amplitude, and also attenuation of single and couple mode vibration in vertical, horizontal, longitudinal displacement directions, then also rocking, yawing, and pitching turning moment directions using the Lumped Parameter method from some references. Analysis and design obtained the dimensions of 3.7 x 1.7 x 0.7 m for shallow foundation system and allowable bearing capacity (qall) indicated equals 4.10 kg/cm2 based on static condition, and 6.20 kg/cm2 according to static and dynamic conditions, respectively. Then, some assessments in static and dynamic calculations were also found the total settlement (D) = 0.49 mm, amplitude (Az) = 6.6 x 10-6 m, (Ax) = 3.2 x 10-6 m, and (Af) = 1.7 x 10-6 rad. Generally, the resulting parameters from those analyses and design have fulfilled the existing standard and local government regulations.